FAKTA SEJARAH DALAM NOVEL RUMPA’NA BONE KARYA ANDI MAKMUR MAKKA (KAJIAN NEW HISTORICISM) - Nurlailatul Qadriani; Arysandi Masda (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2020)
Historical Facts in Rumpa’na Bone Novel by Andi Makmur Makka a New Historicism Study. This research is to understand the historical facts that exist in Rumpa’na Bone novel by Andi Makmur Makka. The type of this research is descriptive qualitative study. The data source of this research is the novel Rumpa’na Bone by Andi Makmur Makka. The analytical method used is the parallel reading technique, by compare with literary texts (novel), and non-literary texts related to events in the analyzed novels. The results include: (1) historical facts in the periode before the collapse of the Bone Kingdom; (2) historical facts are represented through cultural elements, namely siri’culture, royal ceremonies and bissu.